Changes in the circumstances of young mothers in Britain: 1990 to 2000. Issue 10 (15th September 2005) - Nanchahal, Kiran; Wellings, Kaye; Barrett, Geraldine; Copas, Andrew J; Mercer, Catherine H; Macmanus, Sally; Macdowall, Wendy; Fenton, Kevin A; Erens, Bob; Johnson, Anne M
Abstract : Objectives: To assess changes between 1990 and 2000 in the circumstances of women who became mothers before the age of 18. Design: Two cross sectional probability sample surveys of the general population carried out in 1989–1991 (Natsal 1990) and 1999–2001 (Natsal 2000). Setting: British households. Participants: Women aged 18 to 27 years at time of survey (Natsal 1990: 2575, Natsal 2000: 1757). Main outcome measures: Educational attainment, participation in education/work or training, living in social housing, social class, living as lone adult, parity, ill health, and health related behaviours at the time of the interview. Results: The proportion of women who were sexually active before 18 increased between 1990 and 2000 from 58.9% to 71.3% (p<0.0001). There was no significant change in the proportion who had a child before the age of 18 (4.7% in 1990, 5.3% in 2000, p = 0.390). The proportion who had attained no educational qualifications and were not participating in education/work or training was significantly lower in 2000 than in 1990 for all women aged 18–27, but higher among those who were mothers before age 18, although the relative difference was not statistically significant. The proportion living in social housing or reporting a recent long term illness at time of interview was higher and this trend was more pronounced among women who did not experience motherhood before 18 than those who did, but the differences between these groups of women were not statistically significant. Conclusion: Motherhood before the age of 18 continues to be related to a variety of adverse circumstances in adult life, including lack of educational attainment, not being in education/work or training, lone parenthood, and a reduced likelihood of home ownership. There is little evidence of improvement in the circumstances of young mothers between 1990 and 2000 despite improvements in life chances among young women in general.